Pengaruh Model Pembelajaran Role Playing Berbasis Historical Thinking Terhadap Hasil Belajar Peserta Didik Pada Sub Tema Sejarah Lokal - Nita Nathasabilla; Nurul Ratnawati (IAIN Madura, 2025)
Social studies learning in junior high school is designed in an integrated manner and consists of various disciplines such as geography, economics, sociology, and history. One important sub-theme in social studies is local history, which covers past events and figures in the students' surroundings. In studying this sub-theme, students often experience difficulties due to a learning process that tends to emphasize memorization, resulting in suboptimal learning outcomes. This study aims to determine the effect of the historical thinking-based role-playing learning model on student learning outcomes in the sub-theme of local history to address the challenges of social studies learning. The method used is a quasi-experimental nonequivalent control group design. The study was conducted at SMP Negeri 3 Songgon Satu Atap with a sample of 44 students. The instrument test was conducted using validity tests, reliability tests, difficulty level tests, and item discrimination tests. The results of the instrument test showed that most of the items were valid, reliable, and had an easy to moderate difficulty level. In addition, the percentage of discrimination was good as a research instrument. The hypothesis test was conducted with an independent samples t-test using SPSS 29. Based on the research results, it was found that the experimental class experienced a greater increase in learning outcomes, namely 19.83%. Meanwhile, the control class increased by 15.3%. The implementation of the historical thinking-based role-playing learning model had a significant effect on student learning outcomes and could be an alternative in efforts to improve learning outcomes.